Grand Opening of New Fresno County Jail at M and Merced Streets - Watkins, Howard::::::::: (1989)
Fresno County Board of Supervisors' Chair Vernon Conrad speaking at lectern; seated: Superior Court Presiding Judge Frank Creede, former Sheriff Hal McKinney, Sheriff Steve Magarian and others obscured